Impact of the internal training load over recovery-stress balance in endurance runners - Hernández Cruz, Germán; López Walle, Jeanette M.; Quezada Chacón, José Trinidad; Jaenes Sánchez, José Carlos; Rangel Colmenero, Blanca Rocío; Reynoso Sánchez, Luis Felipe (Universitat de les Illes Balears Universitat Autónoma de Barcelona, 2017)
The aim of the research was to analyze the response in the recovery-stress balance perception and the internal training load in resistance runners. 18 trained runners (age: 20.1±2.7 years, weight: 64.2±7.63kg, height, 174.32±6.2cm, VO2max: 57.54±7.34L), participate in tests of 800m (five), 1500m (four), 3000m steeplechase (one), 5000m (five), 10,000m (one) and 21km (two). Three weeks of training monitoring was performed, in which two were of moderate load and one of intense load. The daily S-RPE (Foster et al., 2001) and weekly RESTQ-Sport were applied to evaluate the perception of training load and recovery-stress balance. The Shapiro-Wilk normality test was performed. A variance analysis was applied through the Friedman test, with post hoc Wilcoxon. The Spearmancorrelation coefficient between the RESTQ-Sport scales and the weekly S-RPE was analyzed. The results indicate that the S-RPE presented significant variations between the weeks, with week three reflecting the greater internal training load perceived. With respect to RESTQ-Sport, only the scale Disturbed Breaks (DB) shown significant differences, being this a specific scale of the sport, reflecting an increase in the perception of stress by the intensity of the training. There were no significant correlations, however, the S-RPE and the Disturbed breaks scale increased in week 3. The results coincide with other previous investigations in which the relationship between the increase in the training loads and the perception of this by the athletes.